THE EXCESS OF (MIS) INFORMATION ON HEALTH IN THE MAINSTREAM MEDIA (Fiep Bulletin - online, 2020)
Abstract: The information in the mainstream media in form of opinion, criticism, and superficial interpretation, instead of grounding the knowledge and assisting in making decisions, ends up causing a dispersion of content generating mis founded conclusions. This study aims to verify the influence of the media on the knowledge of women who practice weight training and group fitness classes. A sample of 90 women from 18 to 45 years old answered a questionnaire adapted from Souza (2003, pp. 135-143). The research adopted a quantitative approach, and statistical analysis was used to treat the information. Relating variables of schooling, frequency of the use of the means of communication to obtain health information, application of this information, and verification if it was transmitted by a specialized professional and was scientifically proven. A few variables obtained correlation and, among the correlates, two of them were moderate. We concluded that the new mainstream media like internet and social media reflect strong relation between individuals and the search for health information, showing an efficient communication pattern.